Concentration dynamics of nitric oxide in rat hippocampal subregions evoked by stimulation of the NMDA glutamate receptor - Ledo, Ana (2005)
Nitric oxide (*NO) production in response to stimulation of the NMDA glutamate receptor is implicated not only in the synaptic plasticity in hippocampus but may also participate in excitotoxic cell death. Using *NO-selective microssensors inserted into the diffusional field of *NO in acute hippocampal slices, we describe the *NO concentration dynamics evoked by NMDA receptor activation and report profound differences along the trisynaptic loop of the hippocampus. We measured the oxygen gradient across the slice thickness and conclude that *NO measurements were performed at cell layers experiencing physiological oxygen tensions. Recordings performed at increasing distances from the point of NMDA receptor stimulation resulted in a progressive decrease of *NO signals, reaching undetectable levels for distances >400 microm, supporting the notion of a wide diffusional spread of endogenously generated *NO in the hippocampus. Neither a picoinjection nor a continuous perfusion of NMDA resulted in high steady-state *NO levels; rather all signals were transient, suggesting that cells are able to efficiently respond to high *NO concentrations (typically 200-400 nM) bringing it to very low nM levels; the claimed high micromolar *NO range achieved by excessive stimulation of NMDA receptor may have to be reevaluated. The distinct responses to NMDA receptor stimulation along the trysynaptic loop suggest a differential *NO activity and/or regulation among the hippocampal subregions. These findings may be relevant for the understanding of the role of *NO in physiologic mechanisms in the hippocampus and the differential sensitivity of the hippocampal subregions to NMDA receptor-dependent neurodegeneration